Preserving Darwin’s fox: genomic tools for the conservation of South America’s most endangered canid - Valenzuela-Turner, Cristóbal; Grau, José Horacio; Fickel, Jörns; Förster, Daniel W. (Frontiers in Conservation Science, 2025)
Advances in high-throughput sequencing (HTS) have made it a powerful resource for the conservation of threatened species, providing information at both population and individual levels to inform management decisions. In South America, however, the application of HTS in conservation has been limited, primarily due to challenges in funding and access to advanced genomic equipment and analytical expertise. Darwin’s fox (Lycalopex fulvipes), endemic to Chile’s Valdivian Temperate Rainforest, is the most endangered canid in South America with a small and declining population estimated at less than 1000 mature individuals. Despite its endangered status, significant knowledge gaps remain. Here we highlight the potential of HTS to address these challenges, such as clarifying its taxonomy, demographic history, geographic distribution, population structure, genetic diversity, and pathogen exposure. Integrating molecular data into conservation planning will be pivotal in ensuring the long-term survival of Darwin’s fox by identifying priorities for targeted management interventions, highlighting areas of critical habitat for conservation, and guiding genetic rescue efforts to enhance genetic diversity and resilience.